Climate justice in an intergenerational sustainability framework: A stochastic OLG model - Gianluigi Cisco; Andrea Gatto (Economies, 2021)
Climate justice is conceived as the intertemporal climate equity and equality exchange amongst generations. Sustainability - intended as the interplay amongst the economy, the society, the environment, and the governance - is essential to forge the climate justice theoretical framework. On this base, the study attempts to model the intertemporal choice of the status quo amongst generations in these four domains, making use of an overlapping generations (OLG) model making use of an intertemporal choice framework. The proxies detected are GDP growth (economy), environmental quality (environment), and labor growth, and environmental investment (society) as assumptions. The governance dimension is captured by the difference in wealth between young and old generations. The work aims at replying to the following research question: Which are the conditions for sustainable development such that climate justice holds? The intra-intergenerational exchange is defined in two periods, while the individual provides their preferred economic and environmental choice mix as consumption-saving. This study shows that keeping the business-as-usual scenario, young generations will have to bear the brunt of sustainable development. Additionally, reduced emissions are only achievable with increased efforts by the youth by reducing their leisure and consumption. These facts call for enhanced intergenerational sustainability and climate justice policies.
Keywords: 330; climate justice; commons; environmental quality; intergenerational sustainability; OLG model; overlapping generations; resource governance; technology shock